2014
DOI: 10.4187/respcare.03410
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Mechanics in Mechanically Ventilated Patients

Abstract: Respiratory mechanics refers to the expression of lung function through measures of pressure and flow. From these measurements, a variety of derived indices can be determined, such as volume, compliance, resistance, and work of breathing. Plateau pressure is a measure of end-inspiratory distending pressure. It has become increasingly appreciated that end-inspiratory transpulmonary pressure (stress) might be a better indicator of the potential for lung injury than plateau pressure alone. This has resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
142
0
26

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 61 publications
2
142
0
26
Order By: Relevance
“…When positive pressure is applied to the respiratory system, advance analysis of respiratory mechanics can discriminate the different elements of WOB according to equation of motion: resistive component (the resistance to displacement of a determined gas flow), elastic component (elastic opposition to a determined change of volume) and a threshold load. The threshold load refers to the amount of work required to commence inspiratory flow and it is determined by autoPEEP [10][11][12]. Interpretation of these data can help to tailor MV parameters to match the pathophysiology of the disease according to which component is predominantly compromised.…”
Section: Introductionmentioning
confidence: 99%
“…When positive pressure is applied to the respiratory system, advance analysis of respiratory mechanics can discriminate the different elements of WOB according to equation of motion: resistive component (the resistance to displacement of a determined gas flow), elastic component (elastic opposition to a determined change of volume) and a threshold load. The threshold load refers to the amount of work required to commence inspiratory flow and it is determined by autoPEEP [10][11][12]. Interpretation of these data can help to tailor MV parameters to match the pathophysiology of the disease according to which component is predominantly compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Респіраторна система складається з легень та грудної клітки [5]. Ці дві структури механічно функ-ціонують спільно та послідовно.…”
Section: результати та обговоренняunclassified
“…As inhomogeneous lung injury can dramatically increase local stress (more than doubling local pressure) [26,27], it has been suggested that ΔPL be kept below 10-12 cmH2O to prevent lung injury [28]. Additionally, it is suggested that total lung stress (cyclical stress, ΔPL, added to end-expiratory PL) be limited to less than 20-25 cmH2O to decrease overdistension and prevent VILI by limiting total strain to <2 [28,29]. With widely variable chest wall pressures and elastance, we cannot predict whether we are reaching these thresholds of cyclic and total stress without the use of an esophageal balloon.…”
Section: Introductionmentioning
confidence: 99%